The Problem of Observing Sociotechnical Entities in Social Science and Humanities Energy Transition Research - Büscher, Christian (Frontiers in Sociology, 2022)
The notion of “sociotechnical” is an important concept for interdisciplinary research on the transformation of the energy supply. Different branches of research agree that the provision, transmission, and distribution of energy are not simply a matter of physics. The transformation of the energy infrastructure is significantly a societal project, carried by technical innovation and social change. However, in social science and humanities research the interrelation between technical and social processes is often not explicitly explored, even though the interrelationship is the decisive descriptor that distinguishes sociotechnical entities from their environment. This article examines the merits of enriching the concept of sociotechnical by adding the distinction between tight and loose couplings in technical operations and human activities. While tight couplings are necessary to sustain control, they hamper change, and while loose couplings are necessary to adapt and to uphold choice, they increase complexity. Additionally, the article concludes that the introduction of “smart” technologies—an essential vision of the energy transformation—changes the composition of tight and loose couplings. Technical ideas such as machine learning and artificial intelligence go beyond mere automation. We might as well face a new sociotechnical reality. The introduction of intelligence in systems makes more loose couplings necessary. Paradoxically, this allows for new functionality and services by establishing complex operations while at the same time diminishing control by social systems.